A case of atelosteogenesis. Issue 3 (March 1990) - Temple, K; Hall, C A; Chitty, L; Baraitser, M
Abstract : Atelosteogenesis is a rare chondrodysplasia characterised by rhizomelic short limbed dwarfism, thoracic hypoplasia, multiple joint dislocations, talipes equinovarus, and early death. The diagnosis is confirmed radiologically: short, distally tapering humeri, absent or hypoplastic fibulae, deficient vertebral ossification with coronal clefting, and anarchic ossification of phalanges are characteristic findings. We report a male child with this condition born to first cousin Bengali parents.